Model Pendidikan Islam Berbasis Nilai dan Karakter di PTQ Cahaya Nusantara - Rohmah, Mar-Atin Nabila; Widiyanto, Vian (Lembaga Yasin AlSys, 2025)
Ideal Islamic education should not solely emphasize cognitive aspects such as Qur’anic memorization, but also deeply instill values of adab and spirituality. This study aims to examine a value- and character-based Islamic education model implemented at PTQ Cahaya Nusantara. Employing a descriptive qualitative approach, the research was conducted through field methods, utilizing data collection techniques including interviews, observations, and documentation, which were then thematically analyzed. The findings indicate that PTQ Cahaya Nusantara has successfully integrated Islamic values into the learning process through programs such as halaqah adab, market day, the Organisasi Santri (OSP), and character report cards. Key components contributing to the success of this model include sustained leadership styles, consistent evaluation systems, and a value internalization approach. In conclusion, the educational model at PTQ Cahaya Nusantara represents a holistic approach to Islamic education, centered on the development of noble character, and offers a significant contribution to the advancement of value-based character education models in contemporary Islamic educational institutions.